Spirituality problem in philosophical outlook of Shakarim (Journal of Philosophy Culture and Political Science, 2015)
In this article considered the problem of spirituality in the philosophyof the first professional Kazakh philosopher Shakarim. Shakarim appears atus as the unique phenomenon of a philosophical reflection in which theologicalrepresentations, syncretism and mysticism, front lines scientific andanthropological knowledge are combined. The main subject of philosophizingof Shakarim is the person, to it spiritual searches and reflections ofthe thinker are reduced. The philosopher painfully looks for a way of formationof the person spiritual, this purpose is defined by it the main maintenanceof a human ekzistention. Shakarim defines essence of the person,his nature and appointment in knowledge, and first of all in knowledge oftruth that is the acquired quality of the person. The knowledge of truth isn’tlimited to purely rational knowledge as except scientific knowledge arenecessary penetration of the moral beginning, knowledge of virtue here.
Keywords: Soul; honor; spirituality; conscience; reason; science; religion.